Palembang Songket Fabric Visual Motif - Wijayanti, Fitri; Rohendi Rohidi, Tjetjep; Triyanto, Triyanto (Catharsis, 2019)
Palembang songket fabric visually has various aesthetic forms that are always changing, but always maintain the value of local wisdom. The purpose of this study was to analyze the visual motifs of the Palembang Songket fabric. The method used is a qualitative method with a phenomenological research design. Data collection techniques include observation, interview and document study. The validity of the data in this study uses triangulation, while the data analysis procedure is carried out by collecting data, reducing, presenting, and drawing conclusions. This study was analyzed using De Witt H. Parker's aesthetic theory. The results showed that Palembang Songket visually contained two forms of visual classical motifs and modern visual motifs. Visual classical motifs have characteristics; (1) animal and tumpal motifs, (2) material used is silk thread and gold-plated thread, (3) the colors used are predominantly dark red and gold. While modern visual motifs have characteristics, (1) motifs are more on plants and geometric but do not leave tumapal motifs, (2) materials used are silk thread and copper-coated silk thread, (3) colors used are more diverse, like red, pink, blue, green, and purple. Specifically, the subject of this research was the visual motifs of Palembang's Songket fabric, which experienced continuous visual changes in motifs.